Efektivitas Man-Portable Anti-Tank System Dalam Perang Modern: Studi Kasus Javelin Dan NLAW Dalam Konflik Rusia-Ukraina - Zidan Patrio; Agussalim Burhanuddin (JURNAL HUKUM, POLITIK DAN ILMU SOSIAL, 2023)
The war between Russia and Ukraine has recently been in the international spotlight. One of the things seen is the weapons technology used. The modernization of weapons technology has prolonged the war on both sides. This article will discuss Javelin and NLAW which are types of portable anti-tank missiles and their use in the Russia-Ukraine war. Man-Portable Anti-tank Systems are shoulder-fired missiles that are used to destroy opposing tanks. Weapons such as the Javelin and NLAW are the result of the development of earlier versions of the Anti-Tank Guided Missile. These "fire and forget" type missiles such as the Javelin belong to the third generation ATGM system. The method used in this research is descriptive qualitative. Data will be obtained through literature studies from secondary sources such as books, documents, online articles, and media online. The data obtained will be analyzed descriptively. The results of this study show that Javelin and NLAW missiles are very effectively used by Ukraine in repelling Russian tanks.